A novel approach to improve power management in wireless local area networks. (2018) - Collotta, Mario; Pau, Giovanni
In recent years wireless local area networks (WLANs), which generally consist of many access points (APs), have been deployed rapidly in corporate offices and universities, in order to satisfy user demands for high bandwidth and mobility. However, as a consequence to the spread of wireless devices, there has been also a substantial increase in energy consumption. For this reason, novel approaches are needed in order to optimise the energy consumption of APs. To cope with this problem, this paper introduces a novel approach for an energy-aware management of access networks that, based on the instantaneous traffic intensity, reduces the number of active access devices when they are under utilised. The devices are switched on and off according to the distance value of client with respect to the AP, calculated by using the receiving signal strength indicator (RSSI). The results of real test-bed scenarios reveal that the proposed approach obtains promising performance.